Pengaruh Dana Perimbangan dalam Mengurangi Ketimpangan Pendapatan dan Mendorong Pertumbuhan Ekonomi di Sumatera Utara - Purba, Samuel Fery; Simandjorang, Bonataon Maruli Timothy Vincent (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
North Sumatera has implemented regional autonomy and fiscal decentralization policies in its regional finances. However, North Sumatera is still experiencing social inequality when viewed from the distribution of income and economic growth in various regions. Balancing funds consisting of revenue-sharing funds (DBH), general allocation funds (DAU), special physical allocation funds (DAK physical), special allocation funds for health (DBOK) and special allocation funds for education (DBOP) are expected to reduce income inequality and improve the economy in North Sumatera. This study aims to analyze the effect of balancing funds on income inequality and economic growth in North Sumatera in 2017-2021. This study uses the panel data regression method, with data obtained from BPS North Sumatra and the Directorate General of Fiscal Balance, Ministry of Finance. The findings of this study indicate that DBH and DBOK allocations have a significant effect on reducing income inequality. In addition, DAU, DAK physical, and DBOP have not had a significant impact on reducing income inequality. On the other hand, DBOK and DBOP allocations significantly influence economic growth. Meanwhile, DBH, DAU, and DAK have not had a significant physical impact on the regional economy. The regional government in North Sumatra is expected to restore the function of the balance fund, which is to equalize regional development, reduce income inequality, improve the economy, and improve the welfare of the people. Balance funds are not used for the interests of several parties in personnel expenditures and government office operations.